IMPACT OF PESANTREN ECONOMIC DEVELOPMENT THROUGH GOVERNANCE, PRODUCT COMPETITIVENESS, DIGITAL MARKETING AND ENTREPRENEURIAL INNOVATION - Alfarisi, Salman; Latifah, Siti Nur; Farid, Muhammad; Hidayatullah, Indra (Proceedings of the International Conference of Islamic Economics and Business (ICONIES); Vol 11 No 1 (2025): The 11th International Conference of Islamic Economics and Business (ICONIES 2025), 2025)
In the modern era, Islamic boarding schools are required to not only serve as religious educational institutions, but also as independent and competitive economic entities. This study aims to analyze the impact of governance, product competitiveness, digital marketing, and entrepreneurial innovation on the economic development of Islamic boarding schools. This study is quantitative in nature. The population in this study included all 425 students of the Kyai Syarifuddin Asrama Pusat Islamic Boarding School. To determine the sample size from the population, the Slovin formula was used, resulting in a sample size of 81 respondents. Sampling was conducted using propositional sampling. The data analysis used in this study was multiple regression testing. The results of the study show that pesantren management (p = 0.000), product competitiveness (p = 0.000), digital marketing (p = 0.000), and entrepreneurial innovation (p = 0.007) have an effect on the economic development of the Kyai Syarifuddin Islamic Boarding School.